Effect of acupoint application on T lymphocyte subsets in patients with chronic obstructive pulmonary disease: A meta-analysis. Issue 16 (April 2020) - Wu, Jian-Jun; Zhang, Ying-Xue; Xu, Hong-Ri; Li, Yi-Xuan; Jiang, Liang-Duo; Wang, Cheng-Xiang; Han, Mei
Abstract: Background: The development of chronic obstructive pulmonary disease (COPD) is related to the T lymphocyte mediated inflammatory immune response and immune imbalance. The purpose of this systematic review was to evaluate the clinical efficacy and safety of acupoint application on T lymphocyte subsets in patients with COPD. Methods: We searched CNKI, Wan fang, Chongqing VIP, China Biology Medicine disc, PubMed, the Cochrane Library, and EMBASE for studies published as of Oct. 31, 2019. All randomized controlled trials of acupoint application on COPD patients that met the inclusion criteria were included. The Cochrane bias risk assessment tool was used for literature evaluation. RevMan5.3 software was used for meta-analysis. Results: Eight studies (combined n = 524) qualified based on the inclusion criteria. Compared with routine treatment alone, acupoint application combined with routine treatment can significantly increase the T lymphocyte CD4 + /CD8 + ratio (MD 0.12, 95% CI 0.03-0.21, P < .01, I 2 = 49%), reduce CD8 + T-cells (MD-0.99, 95% CI-1.70-0.28, P < .001, I 2 = 37%), reduce the times of acute exacerbations (MD-0.28, 95% CI-0.35-0.21, P < .001, I 2 = 0), and improve the clinical efficacy (MD 1.30, 95% CI 1.14-1.48, P < .001, I 2 = 39%). Conclusion: Acupoint application can improve the CD4 + /CD8 + ratio and CD8 + T-cells in patients with COPD and has an auxiliary effect in reducing the times of acute exacerbations and improving clinical efficacy. Abstract : Supplemental Digital Content is available in the text